Revisiting Donoghue v. Stevenson: an analysis from the perspective of consumer protection - Amin, Naemah (2009)
This paper aims to analyse the case of Donoghue v. Stevenson from the perspective of consumer protection law with special emphasis on liability for defective product which was the main ratio of the case. Although the principle of manufacturer’s liability for defective product as laid down in Donoghue v. Stevenson may be regarded as the source of the modern law of consumerism, there are limits to its application. Thus the paper examines the adequacy and weaknesses of the principle in Donoghue v. Stevenson in providing protection to consumers injured by defective products. This will necessarily involve a discussion of various elements of the law of negligence, burden of proving fault, recoverable loss and damage and available defences for the defendant. The paper also considers the future of tort of negligence generally and Donoghue v. Stevenson’s rules in particular, in light of the introduction of specific statutes deal with consumer protection in the UK as well as Malaysia.